KEABSAHAN HUKUM PERJANJIAN DALAM MODUS PENIPUAN BARANG COD (CASH ON DELIVERY) - Alief Sabrina Angelita Irawan; Mas Chusna Ilmiyatus Saida (JOURNAL SAINS STUDENT RESEARCH, 2023)
The purpose of the study on the Penelitian Hukum Pembeli Perlindungan Hukum Melalui Sistem Elektronik is to understand how the perjanjian jual-belui system is affected by keabsahan and how the penelitian hukum pembeli is protected against kerugian as a result of rusaknya. Goods that are purchased using an electronic system. When there is any weakness in the selling organization and In a trade transaction, there are obligations and liabilities for the parties involved. Metode The method of research that is used is called Library Research Methodology, or simply Library Research. research conducted in the field, where data is derived from available data Using methods such as reading, studying books, understanding rules for limbs, majalah, law, jurisprudence, and other relevant fields. Based on the methods used, results This study indicates that the decline in sales commissions through electronic systems Nevertheless, see the manner in which the perjanjian is described in Pasal 1230 KUH Perdata. it's the two-party kesepakatan,